Crystallinity-induced shape evolution of Pt–Ag nanosheets from branched nanocrystals. Issue 69 (5th August 2016) - Mahmood, Azhar; Saleem, Faisal; Lin, Haifeng; Ni, Bing; Wang, Xun
Abstract : 2D Pt–Ag nanosheets and 3D Pt–Ag–Cu tetrapods have been selectively synthesized, which were determined by the crystallinity of the nanoseeds. Abstract : Crystallinity offers countless opportunities for the controlled synthesis of multimetallic 2D and 3D nanomaterials. Herein we have successfully synthesized 2D Pt–Ag ultrathin nanosheets through the oxidative etching of twin seeds and 3D Pt–Ag–Cu tetrapods via altering the crystallinity through the incorporation of copper into the Pt–Ag alloy. A better electrocatalytic activity is obtained for the oxidation of formic acid which is 3.8 times higher than that of a commercial platinum catalyst as the stepped surface atom densities are higher on the nanosheets.